IMMUNOHISTOCHEMICAL FEATURES OF ADENOHYPOPHYSIS STILLBIRTHS FROM HIV-INFECTED MOTHERS - Шерстюк С. О. (World of Medicine and Biology, 2014)
Morphological changes of adenohypophysis stillbirths from HIV-infected mothers indicate that he felt highly functional stress for a long period of fetal development, leading to inhibition of its functional state in the form of reduced intensity of luminescence drugs adenohypophysis ICA processed to ACTH, compared with the control. Suppression of the functional activity of the cell population adenohypophysis shows the breakdown of compensatory capacity of which may subsequently cause of severe endokrinopatiy. Inhibition of the functional state of the adenohypophysis stillbirths from HIV-infected mothers is the result of prolonged use of compensatory capacities of the body that can further cause of decompensation in a serious endokrynopatiy.